A Study of Patients With Normal Coronary Angiogram Over A Period of 14 Months in A Military Hospital - Malek, Mohammad Abdul; Rahman, SM Mamunur; Iqbal, Syed Asif; Khan, Zehad; Rahman, Mukhlesur; Sultana, Syeda Aleya; Rahman, Wali-Ur; Bhuiyan, AKM Mohiuddin (University Heart Journal, 2013)
Objectives: The objectives were to study the incidence of the normal coronary artery anatomy, to determine their clinical, electrocardiographic, stress testing, echocardiographic and angiographic characteristics. Methods: This is a retrospective study carried out in cardiac center, Combined Military Hospital, Dhaka, Bangladesh on patients seen during the period from November 2010 to Dec 2011. The coronary artery angiography data was collected by a check list and was revised by the authors. Results: Twelve hundred and two fifty patients who had coronary angiography which showed normal coronary artery or minor coronary artery disease were included in this study. 13% were females. The mean age of the patients was 45.6. 74% patients had one or more coronary risk factors and predominant risk factor was hypertension (31%). More than 50% patients had significant cardiac symptoms and about 40% study subjects were found to have prominent ECG changes which preclude noninvasive tests. Only 38% of study subjects underwent exercise ECG tests, among them 12% had positive ETT. Two hundred and forty nine patients (20%) had normal coronary artery anatomy. Right dominant circulation was found in 79% of the patients. Conclusions: The incidence of normal coronary artery anatomy is similar to those reported in other literatures. Although there are limitations of common noninvasive tests to exclude coronary artery disease, proper clinical evaluation and appropriate use of other noninvasive investigations will definitely reduce the burden of coronary angiogram in patients with angina or suspected ischemic heart disease. DOI: http://dx.doi.org/10.3329/uhj.v8i2.16078 University Heart Journal Vol. 8, No. 2, July 2012